2023
DOI: 10.3389/frph.2023.1165204
|View full text |Cite
|
Sign up to set email alerts
|

Time to first childbirth and its predictors among reproductive-age women in Ethiopia: survival analysis of recent evidence from the EDHS 2019

Abstract: BackgroundBeing a mother for the first time is the most significant event in a woman's life. “Age at first birth” refers to a mother's age in years when she gives birth to her first child. The age of first childbirth has physical, economic, and social implications. However, little is known about this issue in Ethiopia. Thus, this study sought to determine the time to first childbirth and its predictors at a national level.MethodsData were extracted from the 2019 Ethiopia Demographic and Health Survey using STA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…A variance inflation factor and tolerance value were used to check the exitances of multicollinearity between variables. A VIF above 4 or tolerance below 0.25 indicated that multicollinearity might exist (Kitaw & Haile, 2022 , 2023 ). To estimate the variation between clusters, Proportional change variance (PCV), intra‐class correlation (ICC), and Median odd ratio (MOR) were computed.…”
Section: Methodsmentioning
confidence: 99%
“…A variance inflation factor and tolerance value were used to check the exitances of multicollinearity between variables. A VIF above 4 or tolerance below 0.25 indicated that multicollinearity might exist (Kitaw & Haile, 2022 , 2023 ). To estimate the variation between clusters, Proportional change variance (PCV), intra‐class correlation (ICC), and Median odd ratio (MOR) were computed.…”
Section: Methodsmentioning
confidence: 99%
“…Variance inflation factor was calculated to check the exitances of multicollinearity between variables. A VIF above 4 indicates multicollinearity might exist ( 30 , 31 ). Akaike information criterion (AIC) and adjusted R 2 values were computed to select the appropriate model.…”
Section: Methodsmentioning
confidence: 99%
“…9 , 10 The acceleration factor for time to first childbirth among women with secondary and above education level was 1.154 compared with those uneducated women. 11 These emerging patterns have been more appreciated in middle-income countries. For instance, in Brazil, the percentage of first births among advanced maternal-age women doubled between 1994 and 2018, from 7.6% to 15.5%.…”
mentioning
confidence: 99%